Role of Real-World Data in Assessing Cardiac Toxicity After Lung Cancer Radiotherapy - Abravan, Azadeh; Price, Gareth; Banfill, Kathryn; Marchant, Tom; Craddock, Matthew; Wood, Joe; Aznar, Marianne C.; McWilliam, Alan; van Herk, Marcel; Faivre-Finn, Corinne (Frontiers in Oncology, 2022)
Radiation-induced heart disease (RIHD) is a recent concern in patients with lung cancer after being treated with radiotherapy. Most of information we have in the field of cardiac toxicity comes from studies utilizing real-world data (RWD) as randomized controlled trials (RCTs) are generally not practical in this field. This article is a narrative review of the literature using RWD to study RIHD in patients with lung cancer following radiotherapy, summarizing heart dosimetric factors associated with outcome, strength, and limitations of the RWD studies, and how RWD can be used to assess a change to cardiac dose constraints.